Aunt Dimity and the king's ransom [large type] - Atherton, Nancy (Atherton, Nancy. Aunt Dimity series, 2018)
Stranded in a rural inn on England's southeast coast, Lori discovers the location's past as a smuggler hangout before investigating suspicious activities among the living and the dead that may be responsible for ghostly nighttime noises.